I.i.12.o Minutes - Labour Party (Ireland) (1981)
Minutes of a joint meeting of the Administrative Council and Parliamentary Labour Party which took place on 2 Dec 1981 concerning the leaking of internal Party discussion documents. Also includes draft minutes. (8 pp)